Kajian Konseptual Hasil Belajar Siswa dalam Berbagai Aspek dan Faktor yang Mempengaruhinya - Elvira Mulia; Supratman Zakir; Cintia Rinjani; Septi Annisa (Universitas Pesantren Tinggi Darul 'Ulum, 2021)
Implementation of the learning and teaching process is the core of education in schools. There are several factors that influence the teaching and learning process that should be considered by educators to determine strategic steps in the learning process. This study aims to examine the concept of student learning outcomes from various aspects, and examine the factors that influence it. This is a literature review that applies a qualitative descriptive method. The results of this study conclude that there are three aspects of student achievement in learning, namely cognitive aspects, affective aspects, and psychomotor aspects. There are two factors that influence the results of these achievements. First, internal factors, namely physiological factors, psychological factors, physical and psychological maturity factors. Second, external factors, namely social factors, cultural factors, and environmental factors.